Treatment satisfaction, safety, and tolerability of cladribine tablets in patients with highly active relapsing multiple sclerosis: CLARIFY-MS study 6-month interim analysis - Brochet, Bruno; Hupperts, Raymond; Langdon, Dawn; Solari, Alessandra; Piehl, Fredrik; Lechner-Scott, Jeannette; Montalban, Xavier; Selmaj, Krzysztof; Valis, Martin; Rejdak, Konrad; Havrdova, Eva K; Patti, Francesco; et al. (Multiple sclerosis and related disorders, 2022)
Background Multiple sclerosis (MS) is a chronic disabling disease that is associated with negative effects on health-related quality of life (HRQoL) due to reduced physical and psychosocial functioning. Cladribine tablets 10 mg (3.5 mg/kg cumulative dose over 2 years) have been approved for the treatment of adult patients with highly active relapsing multiple sclerosis (RMS). The ongoing CLARIFY-MS study (NCT03369665; EudraCT number: 2017-002632-17) aims to assess the effect of cladribine tablets 3.5 mg/kg on HRQoL of patients with highly active RMS. Objective To report on the design of the CLARIFY-MS study, baseline patient characteristics, and results of a pre-planned interim analysis focusing on treatment satisfaction, safety, and tolerability that includes all data reported till 6 months after start of treatment. Methods The CLARIFY-MS study is a 2-year, open-label, single-arm, prospective, multicenter, phase IV study. Eligible patients with highly active RMS were assigned to receive cladribine tablets 3.5 mg/kg over 2 years. Treatment satisfaction was assessed using the Treatment Satisfaction Questionnaire for Medication (TSQM, v1.4; scale range from 0 to 100, higher values indicating higher satisfaction). Safety assessments, including occurrence of treatment-emergent adverse events (TEAEs; any adverse event reported after drug administration), serious adverse events (SAEs), and lymphocyte counts, were summarized descriptively. Results A total of 482 patients from 85 sites in Europe were treated with cladribine tablets. Mean patient age was 37.4 years, 338 (70.1%) were women, median EDSS was 2.5, and 345 (71.6%) were prior users of disease-modifying therapy (DMT). During the first 6 months after the start of treatment, and before reaching the full dose of cladribine tablets, mean TSQM global satisfaction score for the overall population was 70.4 (standard deviation, ± 18.48). The side effects score was 91.9 (± 17.68), convenience scored 86.6 (± 13.57), and effectiveness was 65.8 (± 21.14). A total of 275 patients (57.1%) reported at least one TEAE and 9 patients (1.9%) had a SAE. The majority of observed lymphopenia cases were of grade 1 or 2; 33 (6.8%) of the total study cohort had grade 3 lymphopenia, and no grade 4 lymphopenia was reported. Conclusion Patients reported high treatment satisfaction (TSQM) with cladribine tablets in this pre-planned interim analysis at 6 months. Few serious, and no unexpected, adverse events were reported, and there were no instances of grade 4 lymphopenia over the first 6 months. These preliminary data indicate good tolerability and convenience of administration of cladribine tablets in patients with highly active RMS.
Keywords: lidé; Adult; Immunosuppressive Agents; lokální recidiva nádoru; prospektivní studie; Personal Satisfaction; Multiple Sclerosis; Tablets; Female; Multiple Sclerosis, Relapsing-Remitting; kladribin; relabující-remitující roztroušená skleróza; tablety; Quality of Life; Humans; Prospective Studies; roztroušená skleróza; Cladribine; ženské pohlaví; imunosupresiva; kvalita života; spokojenost pacientů; Patient Satisfaction; dospělí; Neoplasm Recurrence, Local; osobní uspokojení